Modern Democratic Family: An Ethical And Integrity Private Place to Grow - Paulus Satyo Istandar Tan (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
This research aims to analyze the family's role in forming the younger generation's character in the context of the Modern Democratic Family. The research method used involves analysis of themes, basic principles, and discourse regarding repositioning family roles. The research theme responds to ulama and educational figures' moral and social movements regarding the importance of character education in building ethical individuals with integrity in national life. The basic principles identified explain why character education is integral in building ethical individuals and their integrity in national life. The choice of family as the main focus of research is related to achieving education as a nation's intelligence and the birth of a generation of leaders with character. The research results show that repositioning the role of the family is a fundamental issue, and the responsibility for forming the character of the younger generation should be a collective obligation of the Indonesian people. The main obstacle lies in a wrong understanding of the process of character formation, with society tending to blame the weak role of state institutions in formal education. Awareness of the family's significant contribution to character formation's success or failure is an important key. In conclusion, this research emphasizes the need for a correct understanding of the process of character formation and an emphasis on the active role of the family as the main pillar in producing people who are religious, intelligent, independent, and with character in the future.